Optimization process of disk resonator - Suryanata, Lukas Hari. (2010)
For a microelectromechanical system (MEMS) device such as disk resonator, its design must be optimized before it is fabricated. This report presents part of optimization process of disk resonator using a FEA solver, COMSOL Multiphysics. In the beginning, how MEMS device, particularly disk resonator, is fabricated using photolithography process is explained. It is followed by Q-factor concept and its importance in the design optimization process, and the past works done on disk resonator. Then, simulation procedures using COMSOL Multiphysics in attempt to optimize the design of disk resonator will be listed in details. Next, a preliminary mesh study to find out the optimum mesh size and configuration for the disk resonator simulation is elaborated. After that, a Q-factor analysis on the disk resonator ensues, and followed by investigation on the effect of anchor diameter and capacitive gap size on Q-factor. Anchor diameter in the range of 10 – 650 μm and capacitive gap size in the range of 0.5 – 64 μm are taken into these investigations. Although in the end the Q-factor analysis is unsuccessful to pinpoint accurate result in the expected range in the order of 104, the mesh study and the 2 investigations yielded results that can be used to expound the inaccuracy of the Q-factor analysis result. The mesh study revealed the variance in the result due to different mesh element numbers around 50 – 9500. The investigations revealed the optimum parameters of 240 – 300 μm anchor diameter and 0.5 – 2 μm capacitive gap for a 700-μm-in-diameter disk resonator. In the last section, all the theories and findings are summarized.